Depletion of thymopoietin inhibits proliferation and induces cell cycle arrest/apoptosis in glioblastoma cells - Zhang, Lin (World J Surg Oncol, 2016)
BACKGROUND: Glioblastoma (GBM) is the most malignant nervous system tumor with an almost 100 % recurrence rate. Thymopoietin (TMPO) has been demonstrated to be upregulated in various tumors, including lung cancer, breast cancer, and so on, but its role in GBM has not been reported. This study was aimed to determine the role of TMPO in GBM. METHODS: Publicly available Oncomine dataset analysis was used to explore the expression level of TMPO in GBM specimens. Then the expression of TMPO was knocked down in GBM cells using lentiviral system, and the knockdown efficacy was further validated by real-time quantitative PCR and western blot analysis. Furthermore, the effects of TMPO silencing on GBM cell proliferation and apoptosis were examined by MTT, colony formation, and flow cytometry analysis. Meanwhile, the expression of apoptotic markers caspase-3 and poly(ADP-ribose) polymerase (PARP) were investigated by western blot analysis. RESULTS: This study observed that the expression of TMPO in GBM specimens was remarkably higher than that in normal brain specimens. Moreover, knockdown of TMPO could significantly inhibit cell proliferation and arrest cell cycle progression at the G2/M phase. It also found that TMPO knockdown promoted cell apoptosis by upregulation of the cleavage of caspase-3 and PARP protein levels which are the markers of apoptosis. CONCLUSIONS: The results suggested TMPO might be a novel therapeutic target for GBM.